Association between GRIN2B polymorphism and Parkinson’s disease risk, age at onset, and progression in Southern China - Cui, Can; Li, Hongxia; Bao, Yiwen; Han, Yingying; Yu, Hongxiang; Song, Huan; Zhang, Bei (Frontiers in Neurology, 2024)
Background and objectivesThe role of N-methyl-D-aspartate receptor 2B (GRIN2B) single nucleotide polymorphisms (SNPs) in influencing the risk and progression of Parkinson’s disease (PD) is still unclear. This study aimed to assess the impact of GRIN2B genotype status on PD susceptibility and symptom progression.MethodsWe enrolled 165 individuals with sporadic PD and 154 healthy controls, all of whom had comprehensive clinical data available at the start and during follow-up. We used chi-squared (χ2) analysis to compare the allele and genotype frequency distributions between the patient and control groups. Linear mixed-effect models were employed to investigate the link between the GRIN2B genotype and the progression of motor and cognitive symptoms.ResultsThe prevalence of the GG + GT genotype and G allele was higher in patients compared to controls (p = 0.032 and p = 0.001, respectively). Subgroup analysis revealed that the GG + GT genotype and G allele were significantly more frequently observed in late-onset PD (LOPD) patients compared to early-onset PD (EOPD) patients (p = 0.014 and p = 0.035, respectively). Notably, individuals with the GG + GT genotype exhibited an estimated annual progression rate of 6.10 points on the Unified Parkinson’s Disease Rating Scale (UPDRS), which is significantly higher than that of the TT genotype carriers. Furthermore, the GG + GT carriers showed a markedly rapid progression in rigidity. In addition, the GG + GT carriers demonstrated significantly faster progression rates in rigidity (1.83 points/year) and axial impairment (1.2 points/year) compared to the TT carriers. Notably, the GG genotype carriers exhibited a more rapid decline in recall function.ConclusionThe GRIN2B rs219882 G allele is associated with increased PD susceptibility, particularly in LOPD. The carriers of the GG + GT genotype exhibited more rapid motor symptom progression, with a pronounced impact on rigidity and axial impairment.